The effect of imegery training on increasing shooting accuracy in the 10 m air rifle women's class before Porprov XI in 2022 - Soemardiawan; Nurdin; Anggraeni, F. (JUPE: Jurnal Pendidikan Mandala, 2023)
The research problem is the low ability to shoot air rifles in Class 10 m Air Rifle Women athletes before PORPROV XI 2022, due to the still weak accuracy of the players. This is evident from the various tournaments that have taken part, very rarely athletes are able to shoot on target. Mental imagery is one of the mental exercises that really has an influence on improving performance, especially in shooting.